Process Control Performance Assessment From Theory to Implementation - Ordys, Andrzej; Uduehi, Damien; Johnson, Michael A.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2007)
Process Control Performance Assessment is a practical guide to the application of control benchmarking to real, complex, industrial processes. It presents commercial solutions as well as current and future techniques still under development and contains real full-scale-implementation industrial case studies from the oil and gas, power and chemical industries providing a hierarchical perspective on benchmarks. The effect of benchmarking and control tuning on process performance and revenue optimisation is demonstrated. The most frequently occurring practical issues associated with implementing benchmarking algorithms in industrial processes are discussed in detailed and concise terms and guidelines given for avoiding common problems. The impact of problems like valve stiction and plant-wide disturbances on process performance is reviewed and methods for diagnosing causative fault conditions suggested. The benefit of non-intrusive and intrusive benchmarking techniques for optimising control systems using performance assessment and diagnostic tools is the potential to enhance company operational economics through increased throughput and better product quality. The book is appropriate for industrial and academic control and process engineers who wish to learn about methods of benchmarking through directed study or self study. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.
Benchmarking Concepts: An Introduction -- Economic Auditing of Control Systems -- Controller Benchmarking Procedures — Data-driven Methods -- Controller Benchmarking Procedures — Model-based Methods -- Divided Wall Distillation Column Simulation Study -- Locating the Source of a Disturbance -- Benchmarking Control Loops with Oscillations and Stiction -- Controller Benchmarking Algorithms: Some Technical Issues -- A Look Back and a Look Forward to New Research Directions.
Keywords: Control engineering; Chemical engineering; Calculus of variations; Industrial engineering; Production engineering; Production management; Energy policy; Energy and state; Control and Systems Theory; Industrial Chemistry/Chemical Engineering; Calculus of Variations and Optimal Control; Optimization; Industrial and Production Engineering; Operations Management; Energy Policy, Economics and Management